Sociological factors affecting agricultural price risk management in Australia - Jackson, E.; Quaddus, Mohammed; Islam, N.; Stanton, J. (Royal Sociology Society, 2009)
The highly volatile auction system in Australia accounts for 85 percent of ex-farm wool sales, with the remainder sold by forward contract, futures, and other hedging methods. In this article, against the background of an extensive literature on price risk strategies, we investigate title behavioral factors associated with producers' adoption of price risk-management strategies (specifically futures and forward contracts) for selling wool. This research presents a behavioral model based on Diffusion of Innovations, the Theory of Reasoned Action, and the Theory of Planned Behavior. We found that the auction system is used as a price risk-management tool because other selling methods are considered more risky. We also report on a curious relationship between risk and complexity in terms of wool producers' intentions to use forward contracts. We explored sociological factors in conjunction with focus-group data in an attempt to understand this relationship. This exercise yielded some interesting findings on the impact that trust, habit, social cohesion, and networks have on decision making in the rural community. The significance of this article lies in its application of core sociological theory in a new research context: the Australian wool industry.